Free vibration and buckling of porous power-law and sigmoid functionally graded sandwich plates using a simple higher-order shear deformation theory. (11th October 2019) - Daikh, Ahmed Amine; Zenkour, Ashraf M
Abstract: Free vibration and mechanical buckling of porous functionally graded (FG) sandwich plates is studied in this paper by using a new and simple higher-order shear deformation theory (SHSDT). The present theory accounts for the distribution of transvers shear stresses that satisfy the free transverse shear stress conditions on the upper and lower surfaces of the sandwich plate. The FG sandwich plate is composed of three layers, an isotropic core and two FG face layers. Four porosities distribution and new model of FG sandwich plates based on a sigmoid function are presented. The boundary conditions for the FG sandwich plate are assumed to be simply-supported. Navier's solution is used to obtain the closed-form solutions of FG sandwich plates. The effect of porosity, sandwich plate geometry and inhomogeneity parameter on the buckling and free vibration of FG sandwich plate is investigated.